1987
DOI: 10.1111/j.1600-0765.1987.tb02058.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flurbiprofen on the progression of periodontitis in Macaca mulatta

Abstract: The effect of the nonsteroidal anti‐inflammatory drug flurbiprofen has been studied in the ligature‐induced and spontaneous periodontitis model in the rhesus monkey, Macaca mulatta. Twenty‐four adult monkeys with incipient periodontitis were divided into three disease‐matched groups. Two groups received flurbiprofen at dosages of either 0.27 mg/kg/d or 7.1 mg/kg/d delivered systemically via osmotic minipump. A split‐mouth approach was used, placing ligatures on one side and monitoring the progression of period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 16 publications
(12 reference statements)
8
40
0
Order By: Relevance
“…Evidence that these mediators contribute to the characteristic loss of connective tissue and the alveolar bone that surrounds and supports the tooth root associated with periodontal disease comes from studies that demonstrate inflammatory mediator levels decrease after successful treatment (Offenbacher et al ., 1986; Masada et al ., 1990). Further, administration of antiinflammatory drugs that reduce levels of these mediators can suppress bone and tissue destruction (Offenbacher et al ., 1987), and nonsteroidal antiinflammatory drugs that block prostaglandin synthesis can arrest tissue destruction (Offenbacher et al ., 1987). Finally, removal of dental plaque remains the most effective mechanism of restoring an appropriate innate host response in periodontitis patients (Page et al ., 1997), providing more evidence that the bacterial composition associated with periodontitis is directly responsible for a dysfunctional innate host response.…”
Section: Innate Host Defense Status In Clinically Healthy and Diseasementioning
confidence: 99%
“…Evidence that these mediators contribute to the characteristic loss of connective tissue and the alveolar bone that surrounds and supports the tooth root associated with periodontal disease comes from studies that demonstrate inflammatory mediator levels decrease after successful treatment (Offenbacher et al ., 1986; Masada et al ., 1990). Further, administration of antiinflammatory drugs that reduce levels of these mediators can suppress bone and tissue destruction (Offenbacher et al ., 1987), and nonsteroidal antiinflammatory drugs that block prostaglandin synthesis can arrest tissue destruction (Offenbacher et al ., 1987). Finally, removal of dental plaque remains the most effective mechanism of restoring an appropriate innate host response in periodontitis patients (Page et al ., 1997), providing more evidence that the bacterial composition associated with periodontitis is directly responsible for a dysfunctional innate host response.…”
Section: Innate Host Defense Status In Clinically Healthy and Diseasementioning
confidence: 99%
“…Non‐steroidal anti‐inflammatory drugs (NSAIDs) have been widely researched to modify the host response, and in many studies, it has been demonstrated that NSAIDs reduce the attachment loss in animal and human trials 9‐11 . Some studies 12,13 have demonstrated that the addition of NSAIDs to non‐surgical periodontal treatment can reduce the rate of alveolar bone resorption and gingival inflammation.…”
Section: Host Modulation In Periodontal Therapymentioning
confidence: 99%
“…Furthermore, inflamed periodontal tissues which are undergoing attachment loss and bone resorption contain elevated levels of CO products, particularly PGE 2 and to a lesser extent, thromboxane A2 (TxA2) [7][8][9]. Finally, there are considerable data which demonstrate that drugs which block ARA metabolism serve to both diminish the levels of CO products present within the periodontal tissues and inhibit periodontal inflammation, attachment loss and bone resorption [10][11][12][13][14][15][16][17][18][19][20]. It is significant that these drugs can block host-mediated tissue destruction, even in the presence of microbial challenge.…”
Section: Introductionmentioning
confidence: 99%